The Effect of Cocopeat and Charcoal Combination in Growing Media of Green Mustard (Brassica rapa L.) Var. Parachinensis Growth - Masniar Vina Kesti; Bambang Irawan; Priyambodo Priyambodo; Martha Lulus Lande (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2020)
Green mustard is one type of vegetable that is easily cultivated and has good prospects to increase farmers' income and community nutrition. Growing media is a material that is useful as a place to stand upright seedlings, to develop seedling roots, to store water, gas, and nutrients needed for seedling growth. The purpose of this study is a). to determine the effect of using a combination of cocopeat and charcoal as a medium for planting mustard greens, b). to get the best dosage of the composition of the growing medium on the growth of mustard greens. The study was conducted in a completely randomized design (CRD) with 4 treatments and 6 replications. The data were analyzed by analysis of variance (ANOVA) and further tested with the Least Significant Difference test (LSD) = 5%. The results showed that the use of cocopeat growing media and charcoal influenced germination and vigor index. Cocopeat and charcoal have a significant effect on fresh and dry weight and chlorophyll content of mustard greens. The mixture of cocopeat growing media and charcoal on P1 did not affect the growth of green mustard on the dry weight. Fresh weight gave a significant effect on K1 and P1 was also significantly different from P2 and P3.